Enriching language teaching for the academically talented pupils in grade four - Beltran, Antonia Garcia 1942- (1967)
This study designs a plan for enrichment activities to vitalize language teaching for the academically talented pupils in Grade IV.
Thesis (M.A.T. Special Education)--University of the Philippines, Diliman.
Keywords: Gifted children; Language and languages -- Study and teaching